Effects of dietary sodium on performance, flight and compensation strategies in the cotton bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) - Xiao, Kai (BioMed Central, 2010)
BACKGROUND: Sodium is critical for many physiological functions in insects. Herbivorous insects should expend considerable energy to compensate for sodium deficiency due to low sodium concentration in most inland plants upon which they feed. However, sodium compensation behaviors such as mud-puddling have been observed in some species but not in others. We expect that there may be other sodium compensation strategies in insects. Here, we select a rarely mud-puddling insect species, the cotton boll worm, Helicoverpa armigera, and determine the effects of dietary sodium on performance and flight, and examine their means of sodium compensation. RESULTS: When freshly hatched H. armigera neonates were cultured on one of three diets differing in sodium contents (diet A, B and C with a high, middle and low sodium concentrations, respectively), the larvae on diet C grew larger, had a higher mortality rate and a shorter development period than those on diet A and B. The larvae previously fed from 1(st )to 3(rd )instar on diet C consumed more subsequent diet when they were transferred to diet A or C at 4(th )instar, comparing to those previously fed on diet A. Moreover, any 4(th)-instar larvae on diet C consumed a greater amount of food than those on diet A, no matter which diet the larvae had previously ingested from 1(st )to 3(rd )instar. Moths from diet A and B flew more rapidly than those from diet C, with similar sugar and lipid utilization rates among the three test groups. When a 5(th)-instar cannibal from diet A, B or C and a 5(th)-instar victim from diet A were housed together, many more cannibals from diet C ate their victims. When a victim from diet A, B or C was provided, a cannibal from diet C was more likely to eat the victim from diet A. When newly emerged moths had been exposed to 3% sodium chloride solution for all scotophase period, the average weight increase (proxy for sodium solution intake) for moths from diet A was lower than those from diet B or C. CONCLUSION: Sodium-deficient diet resulted in rapid growth and development of H. armigera larvae, decreased larvae survival, and reduced flight speed of H. armigera adults. To compensate for sodium deficiency, H. armigera ingested a large quantity of larval food, increased larval cannibalism incidence and harvested sodium during the adult stage.